Chemical shielding of closed-shell molecules using extended coupled-cluster theory - Ravichandran, Lalitha; Joshi, Sayali; Vaval, Nayana (International Conference on Recent Advances in Spectroscopy - Theoretical, Astrophysical and Experimental Perspectives, 2010)
In this paper we report calculation of the nuclear magnetic shielding constant using extended coupled cluster response approach. We present the results for the HF, BH, CO and N(2) molecules. These results show importance of correlation corrections for the shielding constant.